2011
DOI: 10.1002/ejoc.201101016
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Aromatic and Aliphatic Esters Using the Reducing Systems MoO2(acac)2 or V(O)(OiPr)3 in Combination with 1,1,3,3‐Tetramethyldisiloxane

Abstract: An efficient reduction of aromatic and aliphatic esters with 1,1,3,3-tetramethyldisiloxane in combination with [MoO 2 -(acac) 2 ] or [V(O)(OiPr) 3 ] is reported. In the former system, the presence of triphenylphosphane oxide allows high conver-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…In this chemistry, after an extensive investigation of a variety of conditions, they employed equimolar TMDS/MoO 2 (acac) 2 or TMDS/V(O)(OiPr) 3 in toluene for 16-24 h with the molybdenum system being preferred. 84 The system of PMHS/V(O)(OiPr) 3 worked well for this reduction as well. The addition of 2 mol % of triphenylphosphine oxide allowed for a reduction of the MoO 2 (acac) 2 charge from 5 to 1 mol % with no loss in yield.…”
Section: Tmds Reduction Of Carboxylic Acidsmentioning
confidence: 96%
“…In this chemistry, after an extensive investigation of a variety of conditions, they employed equimolar TMDS/MoO 2 (acac) 2 or TMDS/V(O)(OiPr) 3 in toluene for 16-24 h with the molybdenum system being preferred. 84 The system of PMHS/V(O)(OiPr) 3 worked well for this reduction as well. The addition of 2 mol % of triphenylphosphine oxide allowed for a reduction of the MoO 2 (acac) 2 charge from 5 to 1 mol % with no loss in yield.…”
Section: Tmds Reduction Of Carboxylic Acidsmentioning
confidence: 96%
“…More recently, we and others reported mild, safe, and efficient reduction procedures by using TMDS12 for the direct conversion of a range of functions such as phosphane oxides,11 nitriles,13 amides,14 nitro,15 esters,16 and ketones17 depending on the nature of the metal catalyst. We have shown that, by using a stoichiometric amount of Ti(O i Pr) 4 , aromatic or aliphatic nitriles could be readily converted into the corresponding primary amines in high yield 13.…”
Section: Resultsmentioning
confidence: 99%
“…This is the case of the reduction of fatty acids using the mild reducing agent tetramethyldisiloxane (TMDS) and a catalytic amount of InBr 3 , leading to yields of 90% (Scheme 3). 39 Other authors used TMDS in 3 ] as catalysts, achieving quantitative conversions, 40 and, in another example, the system Cu(OTf) 2 /TMDS yields quantitative amounts of saturated fatty alcohols from the corresponding fatty acids. 41…”
Section: Reduction To Alcohols Ethers and Aldehydesmentioning
confidence: 99%